Older Age Is Associated with Decreased Levels of VDR, CYP27B1, and CYP24A1 and Increased Levels of PTH in Human Parathyroid Glands - Yi Jiang; Liyan Liao; Jina Li; Larry Wang; Zhongjian Xie (International Journal of Endocrinology)
Parathyroid glands contain the vitamin D receptor (VDR) and 25-hydroxyvitamin D-1α-hydroxylase (CYP27B1) and 24-hydroxylase (CYP24A1), which catalyze the production and degradation of 1,25-dihydroxyvitamin D [1,25(OH)2D], respectively. Previous studies have shown that the serum level of intact parathyroid hormone (iPTH) increases with age. We hypothesized that the expression of CYP27B1 or VDR in parathyroid glands decreases with age, which might account for the increased serum levels of iPTH due to decreased suppression of parathyroid hormone (PTH) secretion by 1,25(OH)2D in older people. To test this hypothesis, we examined relative expression levels of VDR, CYP27B1, CYP24A1, and PTH in specimens from parathyroid glands unintentionally removed during thyroidectomy for 70 patients varying in age from 10 to 70 years. The results showed that there was an inverse correlation between age and VDR, CYP27B1, and CYP24A1 expression (p<0.05). A significant positive correlation between PTH expression levels and age was also observed (p<0.05). These data indicate that older age is associated with decreased levels of VDR, CYP27B1, and CYP24A1 and increased levels of PTH in human parathyroid glands.